Occurrence of toxigenic Fusarium spp. in paddy and sorghum - Neera, Neera; Gopalan, N; Murali, H S (The Indian Journal of Agricultural Sciences, 2020)
A total of 45 cereal samples (35 paddy and 10 sorghum) were collected from Mandya and Mysore districts of Karnataka during March, 2019 to study the mycotoxigenic Fusarium strains present in the field and market samples. All samples were brought to DFRL, Mysore and screened for Fusarium presence by agar plating method on Selective Fusarium Agar (SFA) containing streptomycin (1 mg/ml) with incubation at 25 ± 2°C for 3–5 days. In the study, almost 10 different Fusarium species association was revealed with the collected cereal samples. Fusarium species were micromorphologically identified and further confirmed by PCR-based detection using ITS1 and ITS4 primers followed by sequencing. PCR studies confirmed that all the tested fungal isolates belonged to Fusarium spp. with the amplicon size of 590 bp. NCBI data base confirmed the sequence similarity of 99 % to the genus Fusarium and accession numbers were obtained by submitting the sequences to the GenBank. The study disclosed the diversity in phytopathogenic Fusarium spp. in paddy and sorghum growing in different agro-climatic regions of Mysore and Mandya districts of Karnataka, India.